Simulation of the intervertebral disc degeneration in experimental animals (literature review) - Malyshkina, Svitlana; Dedukh, Ninel; Levshin, Oleksandr; Kosterin, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
In solving a problem of the pathogenesis and pathophysiology of intervertebral disc (IVD) degeneration definite contribution belongs to biomedical research on animals. In this regard the authors have presented an analytical overview of different experimental models. We have dealt with eligible use of the study of degenerative processes in the spine of large quadrupeds, compression and relaxation of the back muscles which significantly increases the load on the spine. In case of stabilization of horizontally aligned spine of large animals (calves, sheep and pigs) this additional loading may be even greater than in humans. It was proved that the bone density of the vertebral bodies in the lumbar spine of sheep, pigs and calf is four times higher than in humans indicating a much greater strain on the lumbar spine in these animals compared with humans. There were some experimental works cited proving that a preferred object for modeling of degenerative spinal changes are rabbits and small laboratory animals — rats and mice. Using them one can trace the development of age-related degenerative changes in IVD in a relatively short time, and to examine changes in the cranial and caudal adjacent functional spinal units. In this article we described different methods of reproduction of degenerative changes in various spine segments of such large animals as rabbits, rats, mice. Violation of biomechanics is related to the conditions of instability or compression, and structural components — to the destruction of IVD, chemical influence, and violation of trophic in IVD. It is emphasized that actually none of the models do not reproduce the situation that arises in IVD as a result of its degeneration. Therefore choosing the model for research one should be guided by specific objectives of the study of IVD degeneration and disorders in functional spinal unit.